Perlindungan Hukum Terhadap Konsumen Yang Terlibat Dalam Transaksi Jual Beli Pada Media Sosial Instagram - Ratna Indah Lestari; Nur Wulan Suci; Eka Maisara Amalia (Jurnal Analisis Hukum, 2022)
In online buying and selling, it can be known as e-commerce, with e-commerce, sellers and buyers can carry out transactions without meeting in person. This study aims to determine legal protection, dispute resolution and rights received by consumers in buying and selling transactions on online media. In this study the authors used empirical research methods. The data taken in the form of secondary and primary data, secondary data obtained from interviews of two informants who have cases related to purchases on Instagram social media. Primary data were obtained from Civil Laws, literature studies and various articles related to the problems studied. The results obtained from this paper that legal protection for consumers who feel aggrieved due to unscrupulous producers has been regulated in Law no. 8 of 1999. However, if the number of the irresponsible business actor cannot be contacted, the consumers who are victims will be able to make efforts to seek compensation for this matter and report it to law enforcement officials.